2020
DOI: 10.4314/mlr.v14i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Towards Effective Models and Enforcement of Corporate Social Responsibility in Ethiopia

Abstract: Corporate Social Responsibility (CSR) is a concept whereby companies regard stakeholder interests in reaching corporate decisions on voluntary basis. Even though CSR is not alien to Ethiopians who are known for their philanthropic and charitable activities, there is no law that expressly requires CSR standards and thresholds. Provisions of the 1960 Commercial Code and other domestic laws show that Ethiopian companies have the option to comply with CSR in their core business strategy and decision making. To tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Ethiopian banks have not yet introduced internal policy documents that deal with corporate social responsibilities and related issues. 114 Although the NBE has issued a Banking Risk Management Guideline that all banks must observe, 115 However, the guideline needs to mention climate change and related risks. This indicates that NBE has not yet started to give due attention to potential risks such as climate change and related risks.…”
Section: National Bank Of Ethiopia's Mandate and Sustainable Financementioning
confidence: 99%
“…Ethiopian banks have not yet introduced internal policy documents that deal with corporate social responsibilities and related issues. 114 Although the NBE has issued a Banking Risk Management Guideline that all banks must observe, 115 However, the guideline needs to mention climate change and related risks. This indicates that NBE has not yet started to give due attention to potential risks such as climate change and related risks.…”
Section: National Bank Of Ethiopia's Mandate and Sustainable Financementioning
confidence: 99%
“…9 Like any other contracts, the validity requirements of a contract such as consent, capacity, object and form need to be complied with. 10 When it comes to the form of an arbitral submission, the Civil Code under its Art-3326(2) requires the arbitral submission to be made in the form 'required by law to dispose without consideration of the right to which it relates.' So, if the arbitral submission relates to the contracts of guarantee, insurance contracts, contracts relating to immovable properties or contracts with a public administration, arbitral submissions relating to these transactions should be made in written form and be registered in case of contracts with public administration and contracts relating to immovables.…”
Section: The Form Of Arbitral Submissionmentioning
confidence: 99%
“…The right to appeal in arbitration should not be limited contractually by the parties because:-i) it is against Article 20(6) of the Constitution, Proclamation No 454/2005 and Proclamation No 25/96 which make out the right and ii) it is also against the public policy and confines the parties' right to due process of law. 10 Even a finality clause excluding appealability of an arbitral award to a regular court is declared by the Federal Supreme Court Cassation Bench as unconstitutional in the case of Danni Drilling and National Mineral Corporation Pvt. Ltd Co. 1 Writing an online critic of this judgment one author accurately suggested that:…”
Section: Finalitymentioning
confidence: 99%
See 2 more Smart Citations